2011
DOI: 10.1007/s11418-010-0503-9
|View full text |Cite
|
Sign up to set email alerts
|

Laevigatbenzoate from Croton laevigatus Vahl.

Abstract: A new trans-clerodane diterpenoid, laevigatbenzoate (1), was isolated from the leaves of Croton laevigatus Vahl. Its structure was established on the basis of spectroscopic analysis, and the absolute configuration was determined by application of the CD excitation chirality method. This compound showed weak cytotoxicity against HeLa cells, with an IC(50) value of 45.4 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As part of our recent research work for bioactive agents from Chinese folk medicine, we collected the branches and leaves of C. laevigatus from Hainan Island and performed an intensive chemical analysis. The present project revealed different chemistries in this plant of Hainan Island from those of the Xinshuangbanna area reported by Zou and Li. , We have demonstrated that the major constituents of C. laevigatus on Hainan Island are two diterpenoids, laevinoids A ( 1 ) and B ( 2 ), which represent a new rearranged ent -clerodane scaffold incorporating an unusual 3/5 bicyclic motif. The absolute structures of 1 and 2 were elucidated via MS, NMR, and X-ray crystallographic data.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…As part of our recent research work for bioactive agents from Chinese folk medicine, we collected the branches and leaves of C. laevigatus from Hainan Island and performed an intensive chemical analysis. The present project revealed different chemistries in this plant of Hainan Island from those of the Xinshuangbanna area reported by Zou and Li. , We have demonstrated that the major constituents of C. laevigatus on Hainan Island are two diterpenoids, laevinoids A ( 1 ) and B ( 2 ), which represent a new rearranged ent -clerodane scaffold incorporating an unusual 3/5 bicyclic motif. The absolute structures of 1 and 2 were elucidated via MS, NMR, and X-ray crystallographic data.…”
mentioning
confidence: 49%
“…It is an ethnomedicinal plant whose leaves and roots are used by the Dai people of the Xishuangbanna area to cure bone fracture, malaria, and stomach ache . Recently, Zou and co-workers have reported their studies on the chemical composition of C. laevigatus in a series of papers, revealing the occurrence of cembrane and clerodane diterpenes, together with flavonoids and monoterpenoid glycosides . Meanwhile, Li et al have also discovered clerodane diterpenoids from this herb .…”
mentioning
confidence: 96%
“…Two new clerodane diterpenoids with acyclic side chain at C-9, ent -3,13 E -clerodadiene-15-formate ( 1 ) and 3 α ,4 α ,15,16-tetrahydroxy- ent - neo -cleroda-13 E -ene ( 45 ), were isolated from the roots of C . sylvaticus [ 12 ] and the roots of C. limae [ 13 ], respectively. Eight new clerodane diterpenoids with butenolide at C-9 ( 2 , 3 , 5 , 13 , 14 , 75 , 91 , 92 ) were obtained from three Croton species ( C. crassifolius , C. glabellus , and C. oligandrus ) [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Roots and leaves of the plant are usually used by the Dai people as a traditional drug for treating fractures, malaria, stomach ache, and wounds received from falling [1]. Phytochemical studies of C. laevigatus have not yet been reported with the exception of diterpenoids with interesting skeletons [2,3].Air-dried ground leaves (20 kg) were extracted with MeOH (3 u 80 L) in order to obtain the crude extract (2120 g) after evaporation in vacuo. The extract was suspended in H 2 O (8.0 L) and fractionated successively with petroleum ether, CHCl 3 , and n-BuOH (3 u 8.0 L).…”
mentioning
confidence: 99%
“…Roots and leaves of the plant are usually used by the Dai people as a traditional drug for treating fractures, malaria, stomach ache, and wounds received from falling [1]. Phytochemical studies of C. laevigatus have not yet been reported with the exception of diterpenoids with interesting skeletons [2,3].…”
mentioning
confidence: 99%